Linking Dissolved Organic Matter to CO2 and CH4 Concentrations in Canadian and Chilean Peatland Pools. Issue 4 (25th April 2023) - Hassan, Mahmud; Talbot, Julie; Arsenault, Julien; Martinez‐Cruz, Karla; Sepulveda‐Jauregui, Armando; Hoyos‐Santillan, Jorge; Lapierre, Jean‐François
Abstract: Peatland open‐water pools can be net carbon (C) emitters within heterogeneous peatland ecosystems that are generally net C sinks. However, the intra‐ and inter‐regional patterns and drivers of CO2 and CH4 production, as well as their link with dissolved organic matter (DOM) quality and quantity, remain poorly understood. We analyzed a range of optical characteristics and chemical variables controlling DOM and CO2 and CH4 concentrations in peatland pools across two regions with contrasting geographical properties (i.e., climate, topography, morphometry, and vegetation cover) of eastern Canada and Chilean Patagonia. We found inter‐regional patterns in CO2, CH4 and DOM concentrations and composition that were coherent with patterns in mean annual temperature and precipitation, and vegetation cover. Cross‐regional patterns of CO2 and CH4 were driven by morphometry, vegetation cover, and protein‐like DOM composition, a proxy of high biological activity, whereas temporal variations of CO2 and CH4 concentrations were further influenced by seasonal changes in humic‐like DOM composition, dissolved organic carbon and nutrients (i.e., total phosphorus and total nitrogen) concentrations, as well as pH and oxygen levels. Our results suggest that geophysical constraints associated with local peat and pool characteristics as well as climate patterns are major drivers of DOM and greenhouse gases concentrations and the links between them in broadly distributed peatland pools. Key Points: Broad‐scale patterns in peatland pools dissolved organic matter (DOM) and CO2 were driven by vegetation cover and pool morphometry Broad‐scale patterns in CH4 were the most responsive among C‐species to long‐term climate averages across regions Protein‐like DOM controls within‐pool greenhouse gases (GHG) concentrations across regions, while humic‐like DOM drives within‐site temporal GHG concentrations